Trade dynamics under geopolitical risk - Makram Khalil; David Osten; Felix Strobel (Deutsche Bundesbank, 2025)
In recent years, major exporting economies experienced rising geopolitical risk. From the perspective of the US and the euro area, we employ detailed product data panels to study the consequences of trading-partner geopolitical risk shocks on bilateral imports. We find that these shocks lower import volumes and raise import prices. The decline in imports is stronger when the shocks hit countries that exhibit greater geopolitical distance to the US and the euro area, or when geopolitical risk shocks hit countries that are under US sanctions. Thus, increasing geopolitical risk triggers dynamics that are conducive to a fragmentation of global trade. A case in point are large effects for geopolitical risk shocks originating in China. We find that US and euro area imports from non-Chinese trading partners are also affected by such shocks, which also owes to US dollar and global oil price movements as well as trading-partner value chain linkages with China.
Keywords: F14; F41; F61; F62; 330; Geopolitical risk; imports; United States; euro area